A 2-DOF Piezoelectric Inchworm Actuator for Precise Positioning. (2nd April 2014) - Hua, Shunming; Liu, Guosong; Lou, Yinghou; Li, Zhiqiang; Meng, Yuming
Abstract : A new rotary-linear inchworm actuator is proposed, where a solid mover can be driven along a vertical axis. The most significant feature of the 2D actuator is that all its flexible hinges for clamping and driving are integrated into a monolithic stator complex. The operational principles of its linear and rotary motion are analyzed. Prototype actuator is manufactured and some main performances are tested. Experimental results about rotary motion are as follows. Angle resolution is 0.3 μ rad, maximum rotational speed is 0.01 rad/s, dynamic torque is 0.38 Nm, and stroke is arbitrary. And those of linear motion are as follows: displacement resolution is 0.019 μ m; maximum velocity and dynamic force are 482 μ m/s and 4 Kgf separately. This proves that the 2D actuator can meet the needs of precise positioning with high force or torque.